+0  
 
0
88
3
avatar

Let $f(x) = 12x^9 + x$. Find $f(3) + f(-3)$. Help needed in 10 minutes please help!!!!!

 Feb 13, 2021
 #1
avatar+1385 
0

f(3)) = 12(3)^9+3

f(-3) = 12(-3)^9-3

 

Notice how the 2 answers are negative of each other. -a + a = 0

So our answer is 0.

 

=^._.^=

 Feb 13, 2021
 #2
avatar
0

Just put x = 3   into the equation to compute the value

   then add the value found when you put  x = -3 into the equation.....

 

12 (3)+ 3       +    12 (-3)9   -3 = 0

 Feb 13, 2021
 #3
avatar
0

Thanks!!!

 Feb 13, 2021

56 Online Users

avatar